2021
DOI: 10.3390/molecules26040842
|View full text |Cite
|
Sign up to set email alerts
|

Lignins Isolated via Catalyst-Free Organosolv Pulping from Miscanthus x giganteus, M. sinensis, M. robustus and M. nagara: A Comparative Study

Abstract: As a low-input crop, Miscanthus offers numerous advantages that, in addition to agricultural applications, permits its exploitation for energy, fuel, and material production. Depending on the Miscanthus genotype, season, and harvest time as well as plant component (leaf versus stem), correlations between structure and properties of the corresponding isolated lignins differ. Here, a comparative study is presented between lignins isolated from M. x giganteus, M. sinensis, M. robustus and M. nagara using a cataly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…The overview of the world literature on alternative cellulose sources has demonstrated that despite the diversity of Miscanthus species and their habitats [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], as well as their wide applications ranging from paper industry to biosynthesis products [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the information on Miscanthus cellulose as the substrate for chemical functionalization into CN is presently quite limited, except for the authors’ single studies.…”
Section: Introductionmentioning
confidence: 99%
“…The overview of the world literature on alternative cellulose sources has demonstrated that despite the diversity of Miscanthus species and their habitats [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], as well as their wide applications ranging from paper industry to biosynthesis products [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the information on Miscanthus cellulose as the substrate for chemical functionalization into CN is presently quite limited, except for the authors’ single studies.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest energetic application of the Miscanthus biomass is the manufacture of fuel pellets. The studies [ 37 , 38 , 39 ] show that the Miscanthus pellets have a lower environmental impact compared to the wood ones, mainly because of less energy consumption during granulation: 1 ton of the Miscanthus pellets produce a carbon footprint of 121.6 kg CO 2 -eq., which is about 8% lower than that of the wood pellets [ 49 , 50 , 51 ]. In order to enhance the heating value, transgenic Miscanthus lines with enhanced lignin content were derived [ 52 ].…”
Section: Miscanthus In Energy Productionmentioning
confidence: 99%
“…Up to 40 tons dry biomass a hectare per annum [22,23] ial crop Single planting Plantation operates for 20-25 years [12,36,37] agricultural practices…”
Section: Ield Capacitymentioning
confidence: 99%
“…Therefore, research activities are directed toward the exploitation of renewable resources not used as food and feed source as well as biomass waste [485]. A broad variety of crop genotypes is under current investigation, among them so-called low-input crops cultivated in arid conditions [486][487][488][489]. Promising data are reported for lignin-based hydrogels and hybrid materials tested regarding their antimicrobial activity [490].…”
Section: Drug Release Concepts Mechanisms and Applications In Stem Cell-based Osteogenesis And Angiogenesismentioning
confidence: 99%